Johnny on the Spot-Chronic Inflammation Is Driven by HMGB1 - Gorgulho, Carolina M.; Romagnoli, Graziela G.; Bharthi, Rosh; Lotze, Michael T. (Frontiers in Immunology, 2019)
Although much has been made of the role of HMGB1 acting as an acute damage associated molecular pattern (DAMP) molecule, prompting the response to tissue damage or injury, it is also released at sites of chronic inflammation including sites of infection, autoimmunity, and cancer. As such, the biology is distinguished from homeostasis and acute inflammation by the recruitment and persistence of myeloid derived suppressor cells, T regulatory cells, fibrosis and/or exuberant angiogenesis depending on the antecedents and the other individual inflammatory partners that HMGB1 binds and focuses, including IL-1β, CXCL12/SDF1, LPS, DNA, RNA, and sRAGE. High levels of HMGB1 released into the extracellular milieu and its persistence in the microenvironment can contribute to the pathogenesis of many if not all autoimmune disorders and is a key factor that drives inflammation further and worsens symptoms. HMGB1 is also pivotal in the maintenance of chronic inflammation and a “wound healing” type of immune response that ultimately contributes to the onset of carcinogenesis and tumor progression. Exosomes carrying HMGB1 and other instructive molecules are released and shape the response of various cells in the chronic inflammatory environment. Understanding the defining roles of REDOX, DAMPs and PAMPs, and the host response in chronic inflammation requires an alternative means for positing HMGB1's central role in limiting and focusing inflammation, distinguishing chronic from acute inflammation.